Pengaruh Perkembangan Ekonomi Digital Terhadap Pendapatan Pelaku Usaha UMKM di Kota Serang - Dina Aulia; Ahmad Hidayatullah; Evendi Evendi; Muhamad Riski; Riki Gana Suyatna (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted with the aim of finding out how economic development is Digital and factors that influence the income of MSME business actors in Serang City. Method The research used is qualitative descriptive research, the data collection method is through observation, interviews, questionnaires and documentation. The informants in this research are MSME business actors in Serang , there are approximately 10,321 MSMEs from various types of businesses spread across Serang Jaya City as research objects. The results of this research show there is a positive and significant partial influence of the digital economy on perpetrators' income MSME businesses in Serang. Meanwhile, factors that support and hinder the MSME sector in the digital economy perspective, namely the ability to know how to use technological media which is a supporting indicator of the success of the digital economy.